The Cradle of Christianity: Judaism, Jesus, and the New Testament: essays in honor of Craig A. Evans - Hatina, Thomas R.; Porter, Stanley E.; Evans, Craig A. (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025, 2024)
This major collection of essays by senior colleagues and friends of Craig A. Evans recognizes his contribution to the field of biblical studies by concentrating upon his areas of research and writing interest. These include: the emergence and characteristics of early Judaism, Jesus and the apostolic tradition, and a variety of other supporting areas in New Testament studies. These essays include both focused studies and challenging theoretical explorations